MICROLEARNING AS A DIGITAL LEARNING STRATEGY IN HIGHER HEALTH EDUCATION: LITERATURE REVIEW - Yunianti, Ni Putu Wendi; Khaerudin; Kusumawardani, Dwi (Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
Microlearning represents an innovative strategy in health education that enhances professional skills, competence, retention, and knowledge acquisition. This approach provides adaptable, personalised, and objective-driven education by utilising digital resources, such as mobile apps, brief videos, and engaging simulations. We conducted the study using the PRISMA approach and the systematic literature review method, utilising data sources from Scopus, PubMed, and Google Scholar. Various sociocultural contexts have highlighted the significance of microlearning, particularly within the fields of nursing, medicine, and pharmacy. This study is groundbreaking as it integrates digital and in-person hybrid learning, enhances technological accessibility, and leverages social media. The advancement of clinical, soft, and digital skills stands out as a central focus. The development of microlearning products for nursing education and their integration into a flexible yet structured learning model are highlighted as key recommendations in the study. This approach holds significant promise for revolutionising health education by tailoring it to meet the diverse needs of the global community.